Governança em compras públicas: um estudo na Secretaria Municipal do Planejamento, Orçamento e Gestão da Prefeitura de Fortaleza - Silva, Leonardo Pereira da (2024)
Government inefficiency in solving problems as a result of poor state governance has demanded improvements in the quality of public services and greater efficiency in the management of resources. In this context, the Tribunal de Contas da União (TCU) began to carry out surveys to learn about the situation of public governance and encourage its organizations to adopt good governance practices. In view of the above, the objective of this study is to evaluate the level of maturity of organizational governance practices within the contracting process of the Secretaria Municipal do Planejamento, Orçamento e Gestão of the City of Fortaleza - SEPOG according to parameters defined by the TCU. It is, therefore, a single case study, with a qualitative approach, which used as data collection instruments the application of questionnaires, interviews and document analysis in order to triangulate the data. The results allowed us to conclude that the vast majority of civil servants have a positive perception in relation to the adoption of governance practices in the SEPOG contracting process, being in an intermediate degree of maturity of governance practices. However, in the triangulation of the findings, some divergences were observed in the data obtained, indicating a lack of knowledge of the existence of certain practices on the part of SEPOG employees. Among the contributions of this study, the present research provides new data on the theme of governance, specifically at the municipal level, in order to improve conducts and propose management models that are more appropriate to the organizational governance structure in the management of public procurement in the Municipality of Fortaleza.